Financing constraints, financial flexibility and firm performance: Based on empirical data of listed A-share listed companies in Shanghai and Shenzhen enterprises in China - Zhao, Pujun; Huang, Minghao (Edelweiss Applied Science and Technology, 2025)
This paper investigates the concept of financial flexibility within the frameworks of financing hierarchy theory and agency theory. It analyzes the intricate relationships among financing constraints, financial flexibility, and firm performance, proposing an integrated research model to elucidate their interdependencies. Specifically, this study delves into the internal mechanisms through which financing constraints influence firms’ capacity to sustain financial flexibility, particularly the utilization of operational cash flows as reserves under varying levels of financial constraints. Furthermore, the study reveals that financial flexibility exerts a significant yet context-dependent impact on firm performance. The extent of this impact is moderated by the degree of financing constraints, with higher levels of constraints amplifying the positive effect of financial flexibility on performance. These findings enrich the existing literature by offering fresh insights into how financing constraints shape firms’ financial decisions and overall performance. The study emphasizes the importance of financial flexibility as a dynamic factor that varies in its impact based on the external financial environment and provides practical implications for managers aiming to optimize their firms’ financial strategies.